2003
DOI: 10.1016/s0014-5793(03)00432-0
|View full text |Cite
|
Sign up to set email alerts
|

pH‐dependent photoautotrophic growth of specific photosystem II mutants lacking lumenal extrinsic polypeptides in Synechocystis PCC 6803

Abstract: The removal of either the PsbU or PsbV protein has been investigated in a cyanobacterial v vPsbO strain and in mutants carrying deletions or substitutions in lumen-exposed domains of CP47. These experiments have demonstrated a functional interaction between the PsbU protein and photosystem II (PSII) in the absence of the PsbO subunit. The control:v vPsbO:v vPsbU strain assembled PSII centers at pH 7.5 but did not evolve oxygen; however, photoautotrophic growth was restored at pH 10.0. In addition, several CP47… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
39
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(42 citation statements)
references
References 36 publications
3
39
0
Order By: Relevance
“…There is no doubt that the PsbA protein provides ligands for coordination of the Mn cluster and that the PsbO protein, which is not absolutely essential for water oxidation in cyanobacteria, helps to stabilize the Mn cluster and also Ca 2+ at the lumenal side of PS II. In addition, it has been shown that in plants the polypeptides PsbP and PsbQ have auxiliary functions in concentrating Ca 2+ and Cl À , while in cyanobacteria the polypeptides PsbU and PsbV, like PsbO, are located on the lumenal side of PS II (Shen et al 1992; Kamiya and Shen 2002;Eaton-Rye et al 2003). However, it is still not clear whether any of the intrinsic subunits of low molecular weight that are present in PS II, in addition to the major polypeptides, are involved in stabilizing the inorganic cofactors required for water oxidation (Debus 1992;Ke 2001).…”
Section: Introductionmentioning
confidence: 99%
“…There is no doubt that the PsbA protein provides ligands for coordination of the Mn cluster and that the PsbO protein, which is not absolutely essential for water oxidation in cyanobacteria, helps to stabilize the Mn cluster and also Ca 2+ at the lumenal side of PS II. In addition, it has been shown that in plants the polypeptides PsbP and PsbQ have auxiliary functions in concentrating Ca 2+ and Cl À , while in cyanobacteria the polypeptides PsbU and PsbV, like PsbO, are located on the lumenal side of PS II (Shen et al 1992; Kamiya and Shen 2002;Eaton-Rye et al 2003). However, it is still not clear whether any of the intrinsic subunits of low molecular weight that are present in PS II, in addition to the major polypeptides, are involved in stabilizing the inorganic cofactors required for water oxidation (Debus 1992;Ke 2001).…”
Section: Introductionmentioning
confidence: 99%
“…strain PCC 6803 by identification of a number of pH-sensitive photosystem II (PSII) mutants that are able to grow photoautotrophically at pH 10 but not at pH 7.5 (8,54). Each of these pH-sensitive strains contains two mutations in PSII, including the absence of either the PsbO or PsbV luminal protein.…”
mentioning
confidence: 99%
“…A mutant lacking proteins of the oxygen-evolving complex of PSII is able to grow at alkaline pH but not at neutral or acidic pH (Eaton-Rye et al, 2003). Furthermore, Synechocystis strains DNdhB, with a non-functional NAD(P)H dehydrogenase complex, and DNdhD3/NdhD4, with an inactivated CO 2 uptake system, grow at pH 8.3, but not at pH 7.5 (Zhang et al, 2004).…”
mentioning
confidence: 99%